A COMPARATIVE STUDY OF THE LEARNING PROCESS AND SOCIO-EMOTIONAL ADJUSTMENT OF GRADE 10 STUDENTS IN GOVERNMENT AND PRIVATE SCHOOLS IN FARIDABAD DISTRICT. - Kumari, Kiran; Gaud, Poonam (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The objective of the present study is to examine the differences in learning process and socio-emotional adjustment between grade 10 students studying in government and private schools in Faridabad district. The secondary school stage is a crucial transitional phase where learners develop essential study habits, cognitive strategies, and socio-emotional competencies that significantly influence their academic success and overall well-being. Using a comparative research design, data were collected from a representative sample of grade 10 students using standardized instruments to assess learning styles and adjustment levels. The findings are expected to reveal differences between government and private school students in terms of academic attitudes, peer relationships, emotional regulation, and adaptability to the school environment. The study further seeks to explore whether school type (government versus private) significantly impacts students’ learning outcomes and socio-emotional development. The results of this study may provide valuable insights to educators, policymakers, and parents in developing effective teaching strategies, supportive learning environments, and promoting student well-being in different types of schools.